جودة الخدمات الإلكترونية في المؤسسات المالية ودورها في تحقيق رضا العملاء: دراسة ميدانية. - عمومن بلخير (University Eloued جامعة الوادي, 2024)
الملخص: تهدف هذه الدراسة إلى تحليل أثر جودة الخدمات الإلكترونية على رضا عملاء المؤسسات المالية الجزائرية ، واعتمدت الدراسة الميدانية على الإستبانة والتي شملت 33 فقرة لجمع المعلومات الأولية من عينة الدراسة المكونة من (500) فرد. كما تم الإستعانة بالمقابلات الشخصية ، وفي ضوء ذلك جرى جمع وتحليل البيانات واختبار الفرضيات باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS ، حيث تم استخدام العديد من الأساليب الإحصائية لتحقيق أهداف الدراسة. وبعد إجراء عملية تحليل بيانات الدراسة وفرضياتها توصلت الدراسة إلى وجود درجة رضا مرتفعة لعملاء المؤسسات المالية عن جودة الخدمات الإلكترونية المقدمة من طرف المؤسسات المالية الجزائرية ، كما أظهرت الدراسة وجود أثر ذو دلالة إحصائية لكل بعد من أبعاد جودة الخدمات الإلكترونية على حدى على رضا العملاء،مع وجود أثر ذو دلالة إحصائية لأبعاد جودة الخدمات الإلكترونية مجتمعة على رضا العملاء، وتوصلت الدراسة إلى جملة من الإقتراحات من أبرزها، ضرورة وضع آليات تمكن المؤسسات المالية الجزائرية من فهم سلوك العملاء إتجاه الخدمات الإلكترونية بهدف تقديم خدمات ذات جودة توافق تطلعاتهم، وضع هياكل تنظيمية تتصف بالمرونة تتلائم مع الإستخدامات المستحدثة في مجال تكنولوجيات المعلومات والإتصال مع التطوير المستمر أنظمة الجودة. Abstract: This study aims to analyze the impact of electronic service quality on the satisfaction of customers of Algerian financial institutions. The study relied on a survey consisting of 33 items to collect primary data from a sample of 500 individuals. Personal interviews were also conducted. Subsequently, data were collected, analyzed, and hypotheses were tested using the (SPSS). Various statistical methods were employed to achieve the study's objectives. Following the data analysis and testing of hypotheses, the study found a high level of satisfaction among customers of Algerian financial institutions regarding the quality of electronic services provided. Furthermore, the study revealed a statistically significant impact of each dimension of electronic service quality individually on customer satisfaction, as well as a statistically significant impact of the combined dimensions of electronic service quality on customer satisfaction. The study concluded with several recommendations, including the necessity for Algerian financial institutions to establish mechanisms enabling them to understand customers' behavior towards electronic services in order to provide quality services that meet their expectations. Additionally, it suggested the implementation of flexible organizational structures that align with emerging uses in the field of information and communication technologies, along with continuous development of quality systems.
أطروحة دكتوراه
Keywords: تكنولوجيا معلومات وإتصال; جودة; خدمات إلكترونية; مؤسسات مالية; رضا عملاء; Information Technology and Communication; Quality; Electronic Services; Financial Institutions; Customer satisfaction